Sonographic Indicators for Treatment Choice and Follow-Up in Patients with Pleural Effusion - Ruza Stevic; Nikola Colic; Slavisa Bascarevic; Marko Kostic; Dejan Moskovljevic; Milan Savic; Maja Ercegovac (Canadian Respiratory Journal)
Aim. The aim of this study was to evaluate the role of thoracic sonography in treatment of pleural effusions and to identify sonographic indicators for surgical intervention. Materials and Methods. This study included 378 patients with pleural effusions. US characteristics of effusions as the echo structure and pleural thickening were analyzed. Regarding the US finding, the diagnostic or therapeutic procedure was performed. Results. The study included 267 male and 111 female patients, an average of 56.7 years. Infection was the most frequent cause of effusion. Two hundred sixty-nine patients had loculated and 109 free pleural effusion. Most frequent echo structure of loculated effusion was complex septate, whereas free effusion was mostly anechoic. Successful obtaining of the pleural fluid without real-time guidance was in 88% and under real-time guidance in 99% patients (p<0.012). There was no significant difference in success rate between free and loculated effusion and regarding the echo structure (p=0.710 and 0.126, respectively). Complete fluid removal after serial thoracentesis or drainage was achieved in 86% patients. Forty-five patients with significantly thicker pleural peel and impairment of the diaphragmatic function than remaining of the group (p<0.001) underwent surgery. Open thoracotomy and decortication was more frequently performed in patients with completely fixed diaphragm and complex, dominantly septated effusions. There is no significant difference in US parameters comparing to patients underwent VATS, but the number of VATS is too small for valid conclusion. Conclusion. Thoracic sonography is a very useful tool in the evaluation of clinical course and treatment options in patients with pleural effusions of a different origin.